Better workers, better elections? Electoral management body workforces and electoral integrity worldwide - James, Toby S. (International Political Science Review)
Building better elections is a central task for the study of democracy and democratisation. Despite this, there have been no cross-national studies on the staff who manage and implement elections: electoral management body (EMB) workforces. This article provides the first macroscopic worldwide picture of workforce characteristics, human resource management practices and employee outcomes, and analyses the effects they have on electoral integrity, based on original international surveys of electoral management bodies (EMBs) (n = 51) and electoral officials (n = 2029). Drawing from the human resource management literature, a framework is developed to explain how these factors might interact with EMB performance. Analysis demonstrates them to be highly related. Adding data on human resource management practices and employee outcomes improves explanatory models designed to predict the performance of EMBs. Chiefly, EMBs that enable greater opportunities for employees to be involved in decision-making processes perform better. Recruitment practices, job satisfaction and levels of stress are also important. - Reproduced.
Keywords: Electoral integrity; Democratisation; Human resource management